2024
DOI: 10.1001/jamainternmed.2023.7660
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-Glucose Cotransporter 2 Inhibitors and Nephrolithiasis Risk in Patients With Type 2 Diabetes

Julie M. Paik,
Helen Tesfaye,
Gary C. Curhan
et al.

Abstract: ImportanceType 2 diabetes (T2D) is associated with an increased risk of kidney stones. Sodium-glucose cotransporter 2 inhibitors (SGLT2is) might lower the risk of nephrolithiasis by altering urine composition. However, no studies have investigated the association between SGLT2i use and nephrolithiasis risk in patients receiving routine care in the US.ObjectiveTo investigate the association between SGLT2i use and nephrolithiasis risk in clinical practice.Design, Setting, and ParticipantsThis new-user, active co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
8
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
1
8
0
1
Order By: Relevance
“…We agree that differences may exist in patient characteristics. Nonetheless, new initiators of GLP1-RA and DPP4i, which were also second-line medications for glucose-lowering medications during the study period, showed reasonably similar characteristics to initiators of SGLT2is even before adjustment via propensity score matching (eTable 2 in Supplement 1), suggesting these medications are reasonable comparators. Propensity score matching based on 57 prespecified baseline covariates further mitigated potential confounding.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…We agree that differences may exist in patient characteristics. Nonetheless, new initiators of GLP1-RA and DPP4i, which were also second-line medications for glucose-lowering medications during the study period, showed reasonably similar characteristics to initiators of SGLT2is even before adjustment via propensity score matching (eTable 2 in Supplement 1), suggesting these medications are reasonable comparators. Propensity score matching based on 57 prespecified baseline covariates further mitigated potential confounding.…”
mentioning
confidence: 73%
“…Regarding the finding of a greater magnitude of risk reduction in patients younger than 70 years, we conducted sensitivity analyses that excluded the Medicare fee-for-service database and used alternative age cutoffs for subgroups (<50 vs ≥50 years; <60 vs ≥60 years) to evaluate the robustness of our findings. These analyses produced consistent results.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…To the Editor We write in response to the recent article by Paik et al on the risk of nephrolithiasis among patients with type 2 diabetes receiving different types of oral antidiabetic drugs. The findings presented in the study are both encouraging and inspiring, suggesting a potential correlation between certain antidiabetic medications and a reduced risk of nephrolithiasis.…”
mentioning
confidence: 99%
“…Regarding the selection of oral antidiabetic drugs, it is essential to acknowledge that drug choice is often dictated by individual patient factors, such as blood glucose levels, lifestyle, and comorbidities. The study highlights differences in patient characteristics among those receiving glucagon-like peptide 1 receptor agonists (GLP-1RAs) or dipeptidyl peptidase 4 inhibitors (DPP4is) compared with those prescribed sodium-glucose cotransporter 2 inhibitors (SGLT2is), with notable variations in the prevalence of chronic kidney disease stages 3 to 4 and concomitant use of diuretics and insulin. Although propensity score matching was used to mitigate confounding variables and systemic biases, the potential limitations of this method still exist, particularly if the distribution of propensity scores in the clinical setting significantly deviates from those observed in the study …”
mentioning
confidence: 99%